The Effect Of Affiliate Loan Guarantees On Cost Of Debt: Evidence From Korea - Woo, Yong-Sang (Journal of Applied Business Research, 2017)
A loan guarantee occurs when a company guarantees payment of an affiliate’s loan. Conflicting arguments regarding loan guarantees provided to affiliates have prevailed. First, some suggest that loan guarantees provided to affiliates would decrease firm value because they are contingent liabilities (Shim, 1996; Berkman, Cole & Fu, 2009). Second, others suggest firm value is high when the amount of loan guarantees provided to affiliates is large because loan guarantees would be regarded as a positive indicator of future cash flow (Lee, 2005). The purpose of this study was to present additional empirical evidence of these arguments.The result of this study showed that cost of debt is high when the amount of loan guarantees provided to affiliates is large. This result indicates that creditors demand higher risk premiums when the amount of loan guarantees provided to affiliates is large because they regard loan guarantees as contingent liabilities. Therefore, this result supports the assertion that loan guarantees decrease firm value.
Keywords: Loan Guarantees; Contingent Liabilities; Cost of Debt